The Dakota Access Pipeline (Dapl): The Political Geographies of a Controversy - W. White, George; V. Millett, Bruce; K. Johnson Maier, Kimberly (Human Geography Journal, 2021)
The Dakota Access Pipeline (DAPL), constructed 2016-2017, is just one of numerous energy pipelines in the United States. As with many pipelines, environmental impact is a potential and a concern, but opposition to the DAPL became more intense than opposition to other pipelines, even reaching the national and international stages. Though competing narratives and the depiction of some actors in the DAPL debate have been elucidated and analyzed, there are still ways to apply theory to explain why the DAPL in particular became such a hot political issue or if this issue did any more than capture the public’s attention for a fleeting moment. Assemblage theory should be able to provide an explanation, but it has different genealogies, some diametrically opposed to one another, and they have not been rigorously applied to real-world situations. By carefully applying assemblage theory to the controversy surrounding the DAPL, this article seeks to simultaneously explain the controversy surrounding the DAPL and refine some of the nuanced concepts comprising assemblage theory.